Grit : the power of passion and perseverance - Duckworth, Angela (2016)
"Why do some people succeed and others fail? Sharing new insights from her landmark research on grit, MacArthur genius grant recipient Angela Duckworth explains why talent is hardly a guarantor of success. Rather, other factors can be even more crucial, such as identifying our passions and following through on our commitments. Drawing on her own story as the daughter of a scientist who frequently bemoaned her lack of smarts, Duckworth describes her winding path through teaching, business consulting, and neuroscience, which led to the hypothesis that what really drives success is not "genius" but a special blend of passion and long-term perseverance. As a professor at the University of Pennsylvania, Duckworth created her own "character lab" and set out to test her theory. Here, she takes readers into the field to visit teachers working in some of the toughest schools, cadets struggling through their first days at West Point, and young finalists in the National Spelling Bee. Finally, she shares what she's learned from interviewing dozens of high achievers--from JP Morgan CEO Jamie Dimon to Bob Mankoff, cartoon editor of The New Yorker, to Seattle Seahawks Coach Pete Carroll. Grit is a book about what goes through your head when you fall down, and how that--not talent or luck--makes all the difference"--
Part I. What grit is and why it matters : Showing up ; Distracted by talent ; Effort counts twice ; How gritty are you? ; Grit grows -- Part II. Growing grit from the inside out : Interest ; Practice ; Purpose ; Hope -- Part III. Growing grit from the outside in : Parenting for grit ; The playing fields of grit ; A culture of grit ; Conclusion.
Includes bibliographical references (pages 285-322) and index.
Keywords: Success; Perseverance (Ethics); Expectation (Psychology); Diligence; Perseverance (Ethics.); Achievement; Aspirations (Psychology); Volition; PSYCHOLOGY -- Personality; EDUCATION -- Professional Development; Diligence; Expectation (Psychology); Perseverance (Ethics); Success; Success; Perseverance; Perseverance -- Passion -- Achievement